What is the influence of BOSQU as a learning medium? - Bausir, Umar; Rahmasari , Elfrida (Universitas Muhammadiyah Malang, 2023)
The use of learning media according to the conditions and needs of students has an influence on learning motivation and mastery of students' mathematical concepts, so teachers need to know the media criteria that must be used so that students can be liked and accepted. Quizizz is one of the learning media in the form of quizzes and is based on 4.0. Teachers can choose Quizizz as a learning media based on games and technology. This study aimed to describe the effect of using Quizizz media on junior high school students learning motivation and mastery of mathematical concepts. This research is pre-experimental quantitative research, namely one group pre-test – post-test design (before and after). The number of samples in this study was 28 students, consisting of one class. The instruments used were questionnaires and test sheets. Data collection techniques were carried out in the form of questionnaires and tests. Based on the results of the research data analysis, it was found that the value of Sig. (2-tailed) learning motivation is 0.000 <0.05. So it can be concluded that there is an influence of Quizizz learning media on student learning motivation. Furthermore, it was found that the value of Sig. (2-tailed) mastery of mathematical concepts is 0.000 <0.05. So it can be concluded that there is an influence of Quizizz learning media on students' mastery of mathematical concepts. 05. So, it can be concluded that there is an influence of Quizizz learning media on student learning motivation. Furthermore, it was found that the value of Sig. (2-tailed) mastery of mathematical concepts is 0.000 <0.05. So it can be concluded that there is an influence of Quizizz learning media on students' mastery of mathematical concepts. 05. So, it can be concluded that there is an influence of Quizizz learning media on student learning motivation. Furthermore, it was found that the value of Sig. (2-tailed) mastery of mathematical concepts is 0.000 <0.05. So it can be concluded that there is an influence of Quizizz learning media on students' mastery of mathematical concepts